Foraging [ behavior and ecology - Brown, Joel S. [ (Joel Steven)] , 1959-; Stephens, David W. , 1955-; Ydenberg, Ronald C. (University of Chicago Press, 2007)
Foraging is fundamental to animal survival and reproduction, yet it is much more than a simple matter of finding food; it is a biological imperative. Animals must find and consume resources to succeed, and they make extraordinary efforts to do so. For instance, pythons rarely eat, but when they do, their meals are large?as much as 60 percent larger than their own bodies. The snake?s digestive system is normally dormant, but during digestion metabolic rates can increase fortyfold. A python digesting quietly on the forest floor has the metabolic rate of thoroughbred in a dead heat. This and rela.